Collapsing glomerulopathy; a review on current studies - Azar Baradaran; Padideh Daneii; Mahshid Imankhan; Mahsa Motieian; Sina Neshat (Journal of Preventive Epidemiology)
Collapsing glomerulopathy is a rare and serious disease that is characterized by a rapid deterioration of kidney function and heavy proteinuria. This disease is a variant of focal segmental glomerulosclerosis (FSGS). The disease is more serious than other types of FSGS, with high risks of renal failure and poor prognosis. Collapsing glomerulopathy is often resistant to immunosuppressive therapy and can rapidly result in renal failure, making diagnosing and managing this disease an enormous challenge.